Efektivitas Penggunaan Media Kartu Bergambar Untuk Meningkatkan Kemampuan Berbicara Anak - Fahruddin Fahruddin; Ika Rachmayani; Baik Nilawati Astini; Nuri Safitri (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This study aims to determine the effectiveness of using picture card media to improve the speaking ability of group B children in Nurul Iman Sekarbela Islamic Kindergarten in the 2021/2022 academic year. This study uses a quantitative experimental pre-experimental design method with a one group pretest-posttest design. The sample in this study was group B children in Nurul Iman Sekarbela Islamic Kindergarten, a total of 15 people consisting of 7 boys and 8 girls. Data collection techniques in the form of observation and documentation. The analysis technique includes effectiveness test, normality test, and statistical hypothesis. The results of the normality test obtained that the significance value of the pretest was 0.200 and the posttest was 0.172 which was more than (>) 0.05, meaning that the data was normally distributed. The results showed that there was a significant effectiveness of the use of picture card media on the speaking ability of group B children in Nurul Iman Sekarbela Islamic Kindergarten in 2021/2022. It can be seen from the significance value of children's speaking ability of 0.000 which is smaller than 0.05 (0.000 < 0.05), which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This means that the use of picture card media is effective in improving the speaking ability of group B children in Nurul Iman Sekarbela Islamic Kindergarten for the 2021/2022 academic year